ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI SALURAN DISTRIBUSI USAHA KECIL MENENGAH (UKM): (Survei Pada Kue Bangkit “Syempana” Di Kota Pekanbaru) - Mela Apniza Putri; Rosmayani Rosmayani; Rosmita Rosmita (VALUTA, 2018)
This research is done on a household industry that can also be categorized as Small-Medium Enterprises that makes tradisional riau pastries that produces product. Kue Bangkit “Syempana” is made in a industrial company which purpose is to conserve that traditional pastries such as Kue Bangkit in Pekanbaru. The Syempana company has its own distribution channel. Trere are 4 indicators of Syempana’s distribution channel which are Market Considerations, Product Considerations, Company Considerations, and Intermediary Considerations. The distribution of the products from producer to consumen will be easier by having an effective distribution channel resulting in satisfacation of the consumen and in the end it will create a long term relation between the producer and the consumen. The type of the research is quantitative research (a research that uses numerical data and process with statistical method). The data was collected by handing out questionnaire, interview, observation, and documentation. The result of the research in evey indicator is good. The writer sugges’ts Syempana to expand ts company and to enhance its product’s taste, packaging and volume.